1978
DOI: 10.1007/bf01976409
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization of celery latent virus

Abstract: Celery latent virus has been isolated from plants of celeriac (Apium graveolens var. rapaceum). Chenopodium amaranticolor and C. quinoa are good assay plants. Celery (A. graveolens var. dulce) and celeriac (13 cultivars tested) did not react with visible symptoms.Fourteen new artificial hosts were found. New systemic symptomless hosts are Anthriscus eerefolium, Nicoliana megalosiphon, Pisum sativum, Spinacia oleracea and Trifolium incarnatum.Systemic symptoms were caused in the pea cultivars Cicero and Dark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…It did not produce symptoms in parsley but caused systemic symptoms in Chenopodium quinoa not expected for celery mosaic and differing from those of the seed-transmitted celery latent virus (Bos et al, 1978). Soon thereafter the virus was found to be prevalent in seed lots of various parsley cultivars and origins.…”
Section: Introductionmentioning
confidence: 97%
“…It did not produce symptoms in parsley but caused systemic symptoms in Chenopodium quinoa not expected for celery mosaic and differing from those of the seed-transmitted celery latent virus (Bos et al, 1978). Soon thereafter the virus was found to be prevalent in seed lots of various parsley cultivars and origins.…”
Section: Introductionmentioning
confidence: 97%
“…After back-inoculation the virus did not produce symptoms in celery or in 13 cultivars of celeriac. It was later identified as the ungrouped seedtransmitted celery latent virus and it was found not to enhance the symptoms of celery mosaic virus in celery (Bos et al, 1978).…”
Section: Time Of Infectionmentioning
confidence: 98%
“…Preliminary reports on celery mosaic potyvirus (CeMV) as the causal virus and on its incidence and distribution were by Bos (1973) and Mandersloot et al (1973), respectively. The seed-borne celery latent virus (CeLV), also found in celeriac, has been further characterized (Bos et al, 1978), and data on 18 viruses other than CeMV found in umbelliferous crops and wild species in the Netherlands, when seeking infection sources of CeMV, are in press (Van Dijk and Bos, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…CeLV has been found in the seventies in seeds and crops of celeriac (Bos, 1973;Bos et al, 1978), celery and leaf celery. Samples tested recently only incidentally contained the virus.…”
Section: Celery Latent Virusmentioning
confidence: 98%
“…The seed-borne celery latent virus (CeLV) (Bos et al, 1978) and parsley latent virus (PILV) (Bos et al, 1979) were accidentally detected in plants of celeriac and parsley, respectively, in which they do not seem to cause economic damage.…”
Section: Introductionmentioning
confidence: 99%